Novel sequential proximal iliopsoas compartment block: A four-in-one block as a primary anaesthetic technique for intramedullary femoral nailing surgery: A retrospective study - Carlos Rodrigues Almeida (Indian Journal of Anaesthesia)
Background and Aims: The fragile elderly population suffering from hip fractures presents an anaesthetic challenge; therefore, widening the armamentarium for surgical treatment should be sought. This retrospective study presents a new primary anaesthetic method for intramedullary femoral nailing (IMFN) surgery in the context of hip fracture: the sequential proximal iliopsoas compartment (SPIC) block. Methods: This single-centre retrospective study involved 25 patients aged 80 or older submitted to IMFN surgery. The patients were given a single-shot SPIC block using a total of 25 ml of ropivacaine 0.5% plus dexamethasone 8 mg administered sequentially in the proximal iliopsoas space, divided equally as per two different sites as a primary anaesthetic technique associated with moderate sedation. The outcome measure was the adequacy of the anaesthetic approach. The one-tailed Wilcoxon signed-rank test compared the preoperative numerical pain rating scale (NPRS) with the NPRS at 24 h and the pre-incision with the maximum intraoperative mean arterial pressure. Results: The patients were successfully anaesthetised, had no vasopressor consumption, had good surgical conditions, and had no complaints recorded. No tachycardia or hypertensive events were noted. No additional opioids were given. No statistically different values were observed when the pre-incisional and intraoperative mean arterial pressure values were compared (P = 0.52), and the preoperative NPRS compared with the NPRS at 24 h showed a statistically significant difference (P < 0.001). Conclusion: The SPIC block combined only with moderate sedation permits adequate anaesthesia while avoiding the significant risk of neuraxial/sympathetic blockade.